Clinical epidemiology and prognostic factors in patients with KPC-producing K. pneumoniae infections: a retrospective cohort study - Feng, Qiangsheng; Song, Yuejuan; Ha, Xiaoqin (Frontiers in Public Health, 2025)
BackgroundThis study aimed to investigate the clinical characteristics, drug resistance patterns, and prognosis of CRKP-infected patients.MethodsThis study evaluated in patients with carbapenemase-producing CRKP infection diagnosed through bacteriological evidence and clinical criteria over a 12-month period.ResultsKPC-producing Klebsiella pneumoniae represented 1.16% of all K. pneumoniae infections, the average patient age was 62.3 ± 20.2 years. Lung infection (58%) was the most common site, followed by bloodstream infection (22%) and urinary tract (11%) infections; 86% were nosocomial. Common comorbidities included cerebrovascular disease/cerebral infarction (23%), lung disease (16%), hematologic diseases/malignancies (12%), and viral pneumonia (12%). KPC-Kp exhibited high resistance (>90%) to most tested antibiotics (including cephalosporins, piperacillin/tazobactam, fluoroquinolones, aztreonam, and carbapenems). Significantly lower resistance was observed only to tigecycline (5.1%) and ceftazidime-avibactam (CAZ-AVI) (4.3%). Non-KPC strains (NDM/VIM/OXA-48; n = 48) showed lower resistance (<50%) to several agents and minimal resistance to tigecycline and CAZ-AVI (0–1.0%); resistance differences between KPC and non-KPC groups were highly significant (p < 0.001). KPC-Kp infection conferred significantly higher in-hospital mortality (46%) than non-KPC infections (10.4%; p < 0.001), with nearly half (48%) of KPC-Kp deaths occurring within 7 days of infection. CAZ-AVI usage within the KPC-Kp group did not significantly improve 28-day survival (0.450 ± 0.132 vs. 0.573 ± 0.076, p = 0.317). Multivariate analysis identified significant independent risk factors for in-hospital mortality: KPC-Kp infection (OR 5.96, p < 0.001), bloodstream infection (OR 8.57, p = 0.006), and ICU admission (OR 3.39, p = 0.006).ConclusionKPC-Kp infections demonstrated high incidence (1.16%), and severe mortality (46% in-hospital). Mortality risk was significantly elevated by KPC-Kp infection, bloodstream infection, and ICU admission, underscoring critical clinical threats.